Arabidopsis mitochondrial voltage‐dependent anion channel 3 (AtVDAC3) protein interacts with thioredoxin m2. Issue 11 (8th April 2015) - Zhang, Min; Takano, Tetsuo; Liu, Shenkui; Zhang, Xinxin
Abstract : Voltage‐dependent anion channels (VDACs) are conserved mitochondrial outer membrane proteins. A yeast two‐hybrid screen identified interaction between Arabidopsis VDAC3 and the chloroplast protein thioredoxin m2 (AtTrx m2). This was confirmed via pull‐down assay. A bimolecular fluorescence complementation assay located the interaction in mitochondria. AtVDAC3 and AtTrx m2 transcripts were expressed in multiple tissues and up‐regulated by abiotic stress. Under NaCl stress, AtVDAC3 overexpression inhibited growth and increased H2 O2 accumulation, while AtTrx m2 overexpression conferred resistance to NaCl and reduced H2 O2 . Results indicate that both AtVDAC3 and AtTrx m2 are involved in ROS signaling and play opposite roles in NaCl stress response. Abstract : We identified thioredoxin m2 (Trx m2) as an interactor of Arabidopsis VDAC3. We localized the interaction between AtTrx m2 and AtVDAC3 to mitochondria. Under NaCl stress, AtVDAC3 overexpression inhibited growth and increased H2 O2 . AtTrx m2 overexpression conferred resistance to NaCl stress and reduced H2 O2 .